PROMOTING HIGHER PRODUCTIVITY IN TERTIARY EDUCATION IN GHANA: AN EMPIRICAL ANALYSIS OF CHALLENGES AND EFFECTIVE IMPROVEMENT STRATEGIES IN THE UNIVERSITY FOR DEVELOPMENT STUDIES (UDS) - Abdulai, R. (UDS International Journal of Development, 2019)
The concept of productivity in tertiary education has been emphasized in recent times. This study examines how productivity can be enhanced in higher learning institutions, using the University for Development Studies (UDS) as a case study. The study objectives included assessing the strength of productivity drivers at UDS, examining challenges to productivity and identifying measures for enhancing productivity at UDS and tertiary education in general. The study was basically descriptive, and used primary and secondary data. Questionnaire was administered to 300 staff of UDS who were sampled using simple random sampling technique. Data was analyzed through the Statistical Package for Social Sciences (SPSS) version 24. The study found that UDS is significantly poised to increase its productivity. This was established based on the findings that suggest that the Institution is strengthening and significantly boosting the factors that drive productivity in tertiary education. Key recommendations include the need for increased adoption of technology in teaching and learning. Keywords: Higher productivity, tertiary institution, technology adoption, University for Development Studies